Karl Marx's Ecosocialism: Capital, Nature and the Unfinished Critique of Political Economy. Kohei Saito. (Nueva York: Monthly Review Press, 2017. 308 páginas) - García Quesada, George I. (2020)
Traducción de reseña: "Steve Knight. Karl Marx's Ecosocialism: Capital, Nature and the Unfinished Critique of Political Economy. Kohei Saito. (Nueva York: Monthly Review Press)".